Essential oils and their constituents as skin penetration enhancer for transdermal drug delivery: a review. (31st December 2014) - Herman, Anna; Herman, Andrzej P.
Abstract: Objectives: In this paper, we focused on essential oils and their constituents as skin penetration enhancers for transdermal drug delivery, mechanism of their action as well as their possible toxicity. Key findings: Essential oils and their volatile constituents can penetrate through the skin as well as enhance penetration of different drug from topical formulation into the lower skin layers using different mechanisms of action based on (1) disintegration of the highly ordered intercellular lipid structure between corneocytes in stratum corneum, (2) interaction with intercellular domain of protein, which induces their conformational modification, (3) increase the partitioning of a drug. After application to the skin, essential oils and their components are rapidly metabolized, not accumulated in the organism and fast excreted what strongly suggest that they can be successfully use as safe penetration enhancers. Summary: Essential oils and their constituents may be preferred over the traditionally used synthetics materials as safe and suitable permeation enhancers to promote the percutaneous absorption of hydrophilic and lipophilic drugs from topical formulation into the lower skin layers.